2004
DOI: 10.1016/j.ijdevneu.2003.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of histidine and imidazolelactic acid on various parameters of the oxidative stress in cerebral cortex of young rats

Abstract: Histidinemia is an inherited metabolic disorder caused by deficiency of histidase activity, which leads to tissue accumulation of histidine and its derivatives. Affected patients usually present with speech delay and mental retardation, although asymptomatic patients have been reported. Considering that the pathophysiology of the neurological dysfunction of histidinemia is not yet understood and since histidine has been considered a pro-oxidant agent, in the present study we investigated the effect of histidin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Furthermore, Borton et al (2017) found that low levels of inflammation increased the relative number of these bacteria in the mouse stomach. It is worth noting that Akkermansia is positively correlated with imidazolectic acid, an antioxidant effect ( Tansini et al, 2004 ). Therefore, we speculate that rabbits exposed to HS have a low immune function, anti-inflammatory response, and the destruction of intestinal mucosal tissue, whereas Akkermansia positively regulates the production of antioxidant metabolites, protects the self-healing of the intestinal mucosal protective layer, and enhances the response to inflammatory reaction damage.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Borton et al (2017) found that low levels of inflammation increased the relative number of these bacteria in the mouse stomach. It is worth noting that Akkermansia is positively correlated with imidazolectic acid, an antioxidant effect ( Tansini et al, 2004 ). Therefore, we speculate that rabbits exposed to HS have a low immune function, anti-inflammatory response, and the destruction of intestinal mucosal tissue, whereas Akkermansia positively regulates the production of antioxidant metabolites, protects the self-healing of the intestinal mucosal protective layer, and enhances the response to inflammatory reaction damage.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous reports have placed more emphasis on the antioxidant capacity of C. limon [4,57,58]. C. limon also contains several constituents such as 3-carene, imidazole, D-limonene, geraniol, and squalene as well as other compounds reported as potent antioxidants that can prevent microsomal lipid peroxide and protein degradation of ROS [59,60,61,62,63], These data are in accordance with our phytochemical study results which highlighted C. limon as a powerful scavenging agent.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the intensity of imidazole lactic acid was significantly reduced in rat renal tissues in the high‐dose group, showing that Cd may affect the metabolism of histidine. Some studies have reported that imidazole lactic acid also has an antioxidant effect (Oya & Yamamoto, ; Tansini et al, ). In the current study, the significantly reduced intensity of imidazole lactic acid in kidneys may be associated with Cd‐induced oxidative stress.…”
Section: Discussionmentioning
confidence: 99%